A multi-scale approach to exploring urban places in geotagged photographs. (September 2015) - Feick, Rob; Robertson, Colin
Highlights: We examine the spatial and thematic properties of geotagged Flickr photographs. Flickr tags were aggregated at multiple scales using hexagonal lattices. Tagging similarity was examined using odds-ratio across multiple scales. Similarity was related to scale of aggregation. Place-specific tagging was observed at local scales in the study area. Abstract: User-generated content (UGC) that contains spatial references, often referred to by the more bounded concept of Volunteered Geographic Information (VGI), is often touted as a potentially revolutionary data source for geographical research. This paper explores the capacity of one increasingly prevalent source of these data, geographically encoded photographs, to capture spatial expressions of place in an urban environment. Geotagged photographs were obtained from the Flickr API to build a geographic database of photographs for the city of Vancouver, Canada from 2001–2012. These data were aggregated to multiple geographic units represented as hexagonal lattices. Spatial patterns of photo aggregation were examined for tessellations that ranged from 0.25 ha to 1024 ha. Tags associated with each photo were also explored through the notion of 'tag-space' at multiple resolutions, or "scales", of analysis through local log-odds ratios. Results indicate a significant interaction between tag-space semantics and spatial aggregation which suggests that consideration of scale effects should be integral to analysis of this type of tagged VGI for exploring citizens' sensing of urban environments. The results indicate further that we may have to reconsider the interaction between encoded meaning, the methods used for extracting such meaning from tag-space, and exogenous and endogenous spatial scales of spatial UGC.